2002
DOI: 10.1143/jjap.41.6440
|View full text |Cite
|
Sign up to set email alerts
|

Protonic Conduction in the Single Crystal of Sc-Doped SrZrO3

Abstract: The protonic conduction of Sc-doped SrZrO 3 (SrZr 1Àx Sc x O 3) in the single crystal form is investigated. The SrZr 1Àx Sc x O 3 crystals exhibit significantly higher conductivity than the pure ones, and the crystal with x ¼ 0:05 exhibits the highest conductivity of those masured. The activation energy of the SrZr 1Àx Sc x O 3 crystal decreases rapidly with increasing Sc 3þ concentration when x 0:05, and increases when x > 0:05. The activation energy of SrZr 0:95 Sc 0:05 O 3 agrees with the energy separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…In LSMH crystal it is observed that the increase in conductivity with temperature from 105°C to 130°C is due to dissociation of water molecule into H + and OH − ions which in turn increase the concentration of charge carriers. Such type of conduction is described as protonic conduction [57]. Beyond 130°C, because of dehydration of water molecule, the conductivity decreases due to the decrease in the concentration of H + and OH − ions as is also observed in the thermal analysis of the crystal (Fig.…”
Section: Variation Of Ac Conductivity With Temperaturementioning
confidence: 64%
“…In LSMH crystal it is observed that the increase in conductivity with temperature from 105°C to 130°C is due to dissociation of water molecule into H + and OH − ions which in turn increase the concentration of charge carriers. Such type of conduction is described as protonic conduction [57]. Beyond 130°C, because of dehydration of water molecule, the conductivity decreases due to the decrease in the concentration of H + and OH − ions as is also observed in the thermal analysis of the crystal (Fig.…”
Section: Variation Of Ac Conductivity With Temperaturementioning
confidence: 64%
“…For an MOCVD, we adopted liquid delivery (LD)-MOCVD technique which was used for (Pb,La)(Ti,Zr)O 3 (PLZT) thin film depositions [4]. MOCVD precursors used in this deposition were Sr(METHD) 2 , Zr(METHD) 4 , and Y(EDMMD) 3 (ADEKA Corp.), which were dissolved in ethylcyclohexane (ECH) at concentrations of 0.…”
Section: Methodsmentioning
confidence: 99%
“…MOCVD precursors used in this deposition were Sr(METHD) 2 , Zr(METHD) 4 , and Y(EDMMD) 3 (ADEKA Corp.), which were dissolved in ethylcyclohexane (ECH) at concentrations of 0. 1-(2-methoxyethoxy)-2,2,6,6-tetramethyl-3,5-heptanedio nate and 6-ethyl-2,2-dimethyl-3,5-decanedionate; respectively.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ac conductivity shown by mixed GTF heptahydrate complex is $ 10 À3 ohm À1 m À1 as has also been reported for other coordination compounds. 28,29 The activation energy Ea was calculated before the transition temperature by using the Arrhenius equation ac ¼ o exp (Ea/kT). Figure 9 shows a plot of ln ac versus 1000/T at 10 kHz just before the transition temperature.…”
Section: Frequency Dependence Of Dielectric Propertiesmentioning
confidence: 99%